Sobre Belas Adormecidas e feminismo: análise de uma narrativa de Stephen e Owen King - Schneider, Sabrine Amalia Antunes (2021)
By reading, the reader enters distant, dystopian and fantastic worlds. Through it, the reader is reflected by the characters‟ intrinsic subjectivity. Through literature, we see the social through timeless writing that reflects the context of its author. For “hes”and “shes” was/are made history, society and literature. When considering literature as a social reflex, this research has, as a general objective, to search the history of women and feminist assumptions to approach the theme within the fictional narrative Belas Adormecidas (2017), by the authors Stephen and Owen King. The theoretical support of the historiography of women was based on the studies of Perrot (2005), on the understanding of a male domination by the words of Bourdieu (2012), in addition to the considerations regarding Paglia (1992). From a feminist perspective, also addressing the studies of Pateman (1993), hooks (1981, 2019), Tilly (2007), Oliveira (2013), Haraway (1991) and Arruzza (2015, 2017) became the theoretical points too worked on in this dissertation. Regarding the narrative elements for analysis, the understanding of the whole novel and the characters was alluded to the writings of Lukács (2009), Forster (1998), Adorno (2003), Brait (2002), Fischer (1983), Kundera (1988) and Candido (2011). The research is characterized as theoretical, considering its objectives as explanatory and its procedure as bibliographic, being classified as qualitative in terms of addressing the problem. When analyzing the corpus of the research, it was found the relationship between female history and feminist concepts related to patriarchy within the narrative, making it possible to verify the authorial neutrality about the plot's actions, which pointed to what was defined here as structural sexism, a patriarchal base still internalized in the social imaginary.